2018
DOI: 10.1088/1757-899x/346/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Impact Behaviour and Energy Absorption of Collapsible Metallic and Non-Metallic Energy Absorbers used in Automotive Applications

Abstract: Abstract. Collapsible impact energy absorbers play an important role of protecting automotive components from damage during collision. Collision of the two objects results into the damage to one or both of them. Damage may be in the form of crack, fracture and scratch. Designers must know about how the material and object behave under impact event. Owing to above reasons different types of collapsible impact energy absorbers are developed. In the past different studies were undertaken to improve such collapsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Experimental studies were done to evaluate the effect of apex angle in the range of 5°-25°. Previous studies [14] showed that increasing structure thickness induces better progressive collapse in glass/epoxy composites. Mamalis et al [15] have performed a numerical study on axial crushing for thin walled fiberglass composites with different apex angles of 5°-20°.…”
Section: Introductionmentioning
confidence: 89%
“…Experimental studies were done to evaluate the effect of apex angle in the range of 5°-25°. Previous studies [14] showed that increasing structure thickness induces better progressive collapse in glass/epoxy composites. Mamalis et al [15] have performed a numerical study on axial crushing for thin walled fiberglass composites with different apex angles of 5°-20°.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, various methods of energy absorption in automotive systems have also been studied. [3]. In automotive, some parts are deliberately sacrificed during a collision.…”
Section: Introductionmentioning
confidence: 99%
“…When a thin-walled steel tube is subjected to an axial compressive load, it can generate either a concertina (axisymmetric buckle) or a diamond (non-axisymmetric buckle). A concertina deformation mode is most efficient energy absorbing mode [ 5 ]. Khan et al [ 6 ] explained that failure mode for thin wall cylindrical composite tube can be divided into three modes; (1) mushrooming failure, (2) brittle fracture of the composite tube and (3) increasing folding and hinging.…”
Section: Introductionmentioning
confidence: 99%